The East Asian Economic Crisis: A Discussion - Ibrahim, Shamsulkamal (1998)
Generally, the ASEAN and other East Asian countries are currently facing a severe economic crisis. It started with a currency crisis across the region triggered when the Thai baht had to be floated on 2 July 1997. It later developed into a stock market crisis and financial crisis, culminating in a full blown economic crisis. The possible causes underlying the crisis revolve around the attitude towards risks and debts, unhealthy practices, and rapid movement of capital with the advent of globalisation. The effects of the crisis generally touches the issues of economic growth, credit crunch, decreasing wealth, unemployment, debt burden, political and social repercussions, and ultimately, uncertainty about the future. The various governments, some with the help of the International Monetary Fund, are taking several measures to overcome the crisis, although some with questionable effectiveness. Nevertheless, looking forward, measures must also be taken to try to prevent and mitigate, even if only partially, such crisis in the future.